PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MEMBERSIHKAN GIGI DAN MULUT DI SD NEGERI 106165 MARINDAL I KAB. DELI SERDANG SUMATERA UTARA - Suharni Pintamas Sinaga; Elseria Saragih; Ismadi Sihombing; Junita Manullang; Liber Napitupulu (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
In order for the family and all of its members to be able to help themselves in the health sector and play a significant role in community activities, clean and healthy living behaviors (PHBS) are all health behaviors carried out out of personal knowledge. Clean and healthy living practices are essentially an effort to share knowledge about healthy living practices through communication channels with other people, groups, or the larger community. Many types of information, such as educational materials to broaden understanding and enhance attitudes and behavior related to a clean and healthy way of life, can be disseminated. Dental caries, which affects more than 90% of the global population, is one of the world's concerns.